2020
DOI: 10.1097/scs.0000000000006546
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Outcomes of Closed Reduction Nasal Bone Fractures With a Surgical Navigation System

Abstract: Background: The most prevalent form of facial bone fractures is nasal fractures. The surgical procedures used for these fractures are relatively simple, but complete correction is not easy because the nasal bone is small and identifying the fracture site by palpation is difficult. This study aimed to investigate the efficacy of intraoperative surgical navigation systems in nasal bone fracture surgery through a prospective analysis. Methods: Between Febr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…4 To achieve better anatomic reduction, some modifications, including intraoperative imaging, ultrasoundguided, the use of C-arm, and mobile fluoroscan, were performed with closed reduction. 6,7 Because of the tear of nasal mucosa in nasal bone fracture, it is easy to bleed in the process of reduction with metal nasal bone fracture reduction forceps. In addition, patients underwent pain and anxiety in the process of closed nasal bone fracture reductions under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 To achieve better anatomic reduction, some modifications, including intraoperative imaging, ultrasoundguided, the use of C-arm, and mobile fluoroscan, were performed with closed reduction. 6,7 Because of the tear of nasal mucosa in nasal bone fracture, it is easy to bleed in the process of reduction with metal nasal bone fracture reduction forceps. In addition, patients underwent pain and anxiety in the process of closed nasal bone fracture reductions under local anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Kun Hwang carried out a retrospective study of 503 cases with diverse fracture of nasal bones and found that closed reduction was done in 93% of the fractured nasal bones, 4% in open reduction, and 3% in no surgical intervention 4 . To achieve better anatomic reduction, some modifications, including intraoperative imaging, ultrasound-guided, the use of C-arm, and mobile fluoroscan, were performed with closed reduction 6,7 …”
Section: Discussionmentioning
confidence: 99%
“…Although the application of intraoperative navigation systems is gradually becoming popular with its real-time confirmation of the bone position and safety in treating facial bone fractures, 15,16 this method has main shortcoming, which is the expensiveness of the navigation system device and its accessories 17 . The 3D printing model rebuilt by superimposing all layers of transverse CT images with bioplastic filaments has been widely applied in maxillofacial surgeries 4 .…”
Section: Discussionmentioning
confidence: 99%
“…The trend of using navigation systems for treating facial bone fractures is increasing. [3][4][5][6][7][8][9][10][11][12] Many hospitals adopted this navigation system due to the high demand for otolaryngologists or neurosurgeons to get a better outcome in treating sinus diseases or brain tumors.…”
mentioning
confidence: 99%
“…Although only a few articles suggest the usefulness of the navigation system in correcting nasal bone fractures, any detailed recommendation has never been discussed. [3][4][5] Some authors suggest that reduction should be performed 1 to 2 weeks after injury, warranting subsidization of posttraumatic soft tissue edema. 13 In the pediatric population, however, closed reduction is recommended as early as possible due to early bony union after trauma.…”
mentioning
confidence: 99%